2012
DOI: 10.1111/apt.12149
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of liraglutide in patients with type 2 diabetes and elevated liver enzymes: individual patient data meta‐analysis of the LEAD program

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
162
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(177 citation statements)
references
References 41 publications
8
162
0
7
Order By: Relevance
“…Yet, the primary analysis was designed as an intention-to-treat analysis. Furthermore, the rate of gastrointestinal adverse effects observed in this study was similar to those reported in the literature, and the rate of patient withdrawal was similar to that observed in larger randomized clinical trials (11,37,38).…”
Section: Limitationssupporting
confidence: 88%
See 2 more Smart Citations
“…Yet, the primary analysis was designed as an intention-to-treat analysis. Furthermore, the rate of gastrointestinal adverse effects observed in this study was similar to those reported in the literature, and the rate of patient withdrawal was similar to that observed in larger randomized clinical trials (11,37,38).…”
Section: Limitationssupporting
confidence: 88%
“…Prior studies suggested that GLP-1 receptor agonists, such as liraglutide and exenatide, would improve liver steatosis in animal models (27,28), in human case series (29), and in prospective nonrandomized trials (30,31). However, in the setting of the randomized controlled trial Liraglutide Efficacy and Action in Diabetes (LEAD)-2 substudy, there was a nonsignificant trend toward a reduction in liver steatosis as assessed by computed tomography with the liver-tospleen attenuation ratio, but only for the 23 patients receiving higher doses (1.8 mg) of liraglutide (11,32). It is possible that the postprandial increase in insulin secretion in the portal circulation and the decrease in glucagon secretion induced by the GLP-1 analogs could favor lipogenesis and therefore explain the lack of effect of liraglutide on hepatic steatosis observed in the current study.…”
Section: Effect Of Insulin Glargine and Liraglutide On Mr-based Biomamentioning
confidence: 99%
See 1 more Smart Citation
“…As already discussed for exenatide, this effect appears to be mediated by the favourable action of liraglutide on weight loss and glycaemic control [66] . Furthermore, a few data support a beneficial impact of liraglutide on liver inflammation markers in NAFLD patients with T2DM [67] , in obese women with polycystic ovary syndrome and NAFLD [68] and in one T2DM patient with concomitant cryptogenic cirrhosis [69] .…”
Section: Hepatic Safetymentioning
confidence: 69%
“…As part of studies powered to detect changes in glycaemic control in patients with type 2 diabetes and NAFLD, they caused a reduction in intrahepatic lipid as measured by MRS in addition to reductions in body weight and improved glycaemic control (98). In a separate analysis of type 2 diabetic patients treated with Liraglutide, there was a dose-dependent but non-significant improvement in hepatic steatosis, measured by liver-spleen attenuation ration as well as improvements in abnormal liver function tests (99). In an open-label study, a small cohort of patients with biopsy-proven NAFLD and diabetes were treated with exanatide, 3/8 had a histological improvement after 28 weeks of treatment (100).…”
Section: Glucagon-like Peptide-1mentioning
confidence: 99%